The Relationship Between Parents Level of Knowledge Regarding Topical Fluoride and the Prevalence of Dental Caries in Children Aged 9–11 Years - shafa adilla putri mahesa; Djuned Prasonto; Fathimah Azzahra Attamimi; Siti Nur Riani (YARSI Dental Scientific Meeting - e Journal, 2026)
Background: Dental caries is a significant oral health issue among school-aged children. Parental knowledge plays a crucial role in shaping children's oral health behavior, including preventive efforts through topical fluoride application. Purpose: This study aims to determine the relationship between parental knowledge regarding topical fluoride and dental caries prevalence in children aged 9-11 years at SDN Kelapa Gading Timur 01 North Jakarta, as well as its review from an Islamic perspective. Research method: The research method used is a correlational study with a quantitative approach, where knowledge data were collected via questionnaires and caries data through clinical examinations using DMFT and deft indices, subsequently analyzed with the Spearman correlation test. Results: The results showed that the level of parental knowledge was in the fair to good category and the prevalence of dental caries in children was in the low to moderate category. Statistical analysis revealed significant relationship between parental knowledge regarding topical fluoride and the prevalence of dental caries in the study subjects (p < 0.05). From an Islamic perspective, efforts to prevent dental caries are a form of parental responsibility in maintaining the child's physical health as an amanah (mandate) from Allah SWT. Keywords: Parental Knowledge, Topical Fluoride, Dental Caries, DMFT